The impact of a self-avatar on cognitive load in immersive virtual reality - Steed, Anthony; Ye Pan; Zisch, Fiona; Steptoe, William (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
The use of a self-avatar inside an immersive virtual reality system has been shown to have important effects on presence, interaction and perception of space. Based on studies from linguistics and cognition, in this paper we demonstrate that a self-avatar may aid the participant's cognitive processes while immersed in a virtual reality system. In our study participants were asked to memorise pairs of letters, perform a spatial rotation exercise and then recall the pairs of letters. In a between-subject factor they either had an avatar or not, and in a within-subject factor they were instructed to keep their hands still or not. We found that participants who both had an avatar and were allowed to move their hands had significantly higher letter pair recall. There was no significant difference between the other three conditions. Further analysis showed that participants who were allowed to move their hands, but could not see the self-avatar, usually didn't move their hands or stopped moving their hands after a short while. We argue that an active self-avatar may alleviate the mental load of doing the spatial rotation exercise and thus improve letter recall. The results are further evidence of the importance of an appropriate self-avatar representation in immersive virtual reality.